La motivación y satisfacción laboral en trabajadores en la producción académica desde el año 2010 a 2021. (2021)
The purpose was to describe the relationship between motivation and job satisfaction registered in academic production through articles published in the last 12 years (2010-2021) because it is considered that in this period, globalist government policies have been implemented that generate consequences for organizations. and within them for the motivation and job satisfaction of the collaborators. The method is qualitative, descriptive, transversal and corresponds to a phenomenological-hermeneutical design. A scoping review style document review was established to guide the search for available literature related to the proposed objectives. The main results reflect that the countries with the highest production are Mexico and Chile, with eight each, followed by Colombia with four, Peru with three, Spain and Argentina with two and with a mention Costa Rica, Cuba and Ecuador. It should be noted that 2 of the studies have been carried out between two countries, one includes Chile-Venezuela (2019) and the other Argentina-Brazil (2020).